2019
DOI: 10.1123/ijspp.2018-0221
|View full text |Cite
|
Sign up to set email alerts
|

Cycling at Altitude: Lower Absolute Power Output as the Main Cause of Lower Gross Efficiency

Abstract: Background: Although cyclists often compete at altitude, the effect of altitude on gross efficiency (GE) remains inconclusive. Purpose: To investigate the effect of altitude on GE at the same relative exercise intensity and at the same absolute power output (PO) and to determine the effect of altitude on the change in GE during high-intensity exercise. Methods: Twenty-one trained men performed 3 maximal incremental tests and 5 GE tests at sea level, 1500 m, and 2500 m of acute simulated altitude. The GE tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Less efficiency for a given work output is attributed to the higher energy cost of exercise [31,32]. Hypoxic conditions may decrease mechanical efficiency, but the results of previous studies are still inconclusive [23,33,34]. Noordhof et al [35] proposed that the reduction of GE under hypoxic conditions could be caused by an increased cost of ventilation and HR in combination with a higher respiratory-exchange ratio (RER) during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Less efficiency for a given work output is attributed to the higher energy cost of exercise [31,32]. Hypoxic conditions may decrease mechanical efficiency, but the results of previous studies are still inconclusive [23,33,34]. Noordhof et al [35] proposed that the reduction of GE under hypoxic conditions could be caused by an increased cost of ventilation and HR in combination with a higher respiratory-exchange ratio (RER) during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…This power dissimilitude at sea level and altitude was already addressed by van Ingen Schenau in the early nineties of the last century [18]. More recently, Van Erck et al [19] showed that a reduction in gross efficiency of athletes is connected to the lower power output at altitude. The fact that the existing world records in speed skating have been accomplished at the higher elevation rinks of Calgary and Salt Lake City shows that despite the lower power output the lower density at altitude prevails.…”
Section: Looking Closer At the 1998 Nagano Resultsmentioning
confidence: 88%
“…In the study of Van Erck et al [19], 21 trained male cyclists were tested at sea level and at 1500 and 2500 m simulated altitude. Participants were instructed to perform a time trial of 4000 m and to complete it as fast as possible, giving average power output values of 317 (±26)W at sea level, 286 (±32)W at 1500 m and 255 (±23)W at 2500 m. In terms of exertion, this seems to come closest to completing a 5000 m race in speed skating.…”
Section: Looking Closer At the 1998 Nagano Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of biomechanics, researchers studied kinematics, kinetics and EMG to explore motion control mechanics and improve cycling performance [7]. Most of these studies focused on the effects of changing workload [8], pedaling cadence [8,9], power output [10][11][12][13][14][15][16], EMG [17][18][19][20][21][22][23] and gross efficiency [24][25][26] when cyclists were riding on level terrain, while there was much less research focused on cycling in either uphill or downhill conditions. Cycling on a surface with different slopes could help us to examine how the central nervous system (CNS) responds to different tasks in the musculoskeletal system, by monitoring muscle activity, joint moments, or works.…”
Section: Introductionmentioning
confidence: 99%